Síntese de macrociclos derivados de D-glicosamina. - Magno Carvalho Pires (2009)
The macrocycles form an important class of compounds that, by having various biological activities and many drugs available, are targets of intense research. The challenge of synthesizing macrocycles via short and efficient synthetic routes, with yields that made possible the assessment of organic compounds, were the goals of this work.Two glycosides were synthesized from D-glucosamine by four steps. These glycosides were submitted to Bu3SnH/AIBN-mediated radical carbocyclization reactions to furnish three macrocycles and two products of aromatic radical substitution.